A Multi-Instance, Multi-Timestep Co-Simulation Approach for Power System Simulation Tools - Scheibe, Christian; Leugner, Johannes; Mehlmann, Gert; Luther, Matthias (2022 IEEE International Conference on Power Systems Technology: Embracing Advanced Technology in Power and Energy Systems for Sustainable Development, POWERCON 2022, 2022)
This paper proposes a Co-Simulation concept that couples two or more simulators utilizing different timesteps. The interprocess communication is handled via a shared memory based algorithm. Unfavorable effects due to the conversion between time steps are eliminated using filters. The electrical representation is based on a Bergeron line model utilizing the dependency of time and location of travelling waves along transmission lines. The proposed Co-Simulation has minimal impact on accuracy while greatly reducing simulation execution time.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Co-Simulation; Electromagnetic Transients; Shared Memory; Transmission Line Models